STRESSED OUT IN WHITE COATS: A STUDY ON PERCEIVED STRESS AND STRESSORS IN UNDERGRADUATE MEDICAL STUDENTS - Goswami, Choitali; Panja, Saumabrata; Bose, Tapas Kr (Journal of Forensic Medicine and Toxicology, 2025)
Stress among medical students across the world has emerged as a major cause of concern over last few years. Multiple studies across the globe have shown a significant high stress level among medical students. This cross-sectional study was conducted in a medical college in eastern India among one hundred and twenty eight medical undergraduate students in their seventh semester. Data was collected using self-administered questionnaire for demographic details, academic, psychosocial and environmental stressors and perceived stress scale (PSS). Out of the 128 students who participated, 72 (56.25% ) were female and 56 (43.75%) were male. The mean perceived stress score was 27.18 +/- 5.68. The median perceived stress score of the observations was 28. Mean perceived stress scores among female and male medical students were 28.52+/- 5.42 and 25.82+/- 5.15 respectively. Majority of both male and female students reported moderate degree of perceived stress followed by severe stress in a significant percentage of students. Academic pressure was identified as the most predominant stressor in majority of students followed by psychosocial issue like loneliness. Establishment of dedicated counseling cell and periodic mental health awareness programs should be organized for both students and teachers. Besides educating the students in a professional medical course, it is equally important to teach them self care and stress management skills. A holistic approach is essential to shape a medical student into a physically and mentally healthy physician.